Effects of nanoparticle aggregation, particle size and temperature of nanofluids using molecular dynamics simulation / Lee Soon Li - Lee, Soon Li (2016)

(untitled)
Nanofluids have emerged as potential alternative for next generation of heat transfer fluids by suspending 1-100nm sized nanoparticles into conventional heat transfer fluids to enhance its inherent poor thermal conductivity. Consequently, the main concern of this novel exploitation is based on the fact that there is no established physical fundamental to explain the observed enhanced thermal conductivity and there are controversial laboratories results reported. To make matters worse, the enhanced thermal conductivity in nanofluids is always accompanied by an increase in viscosity. In order to fill the research gap, the objective of this thesis is to study potential mechanisms in enhancing thermal transport of nanofluids, namely Brownian motion of nanoparticles, Brownian motion induced mirco-convection in base fluids and effects of nanoparticle aggregation. Apart from this, efficiency of nanofluids (ratio of thermal conductivity and viscosity enhancement) against particle size and temperature effects was also investigated. Several reasons that contributed to the conflicting reported data on thermal conductivity and viscosity include the poor characterisation on nanofluids especially sample polydispersity and difficult-to-measure hydrodynamic particle size distribution. For that reason, molecular dynamics simulation using Green Kubo method was employed in this research to perform an ideal experiment with controlled dispersity of copper-argon nanofluids. The roles of Brownian motion of nanoparticles and its induced micro-convection in base fluid were determined by studying the effects of particle size on the thermal conductivity and diffusion coefficient. Results showed that the Brownian motion and induced micro-convection had insignificant effects to enhance thermal conductivity. Based on microscopic analysis, the hydrodynamic effect was restricted by amorphous-like interfacial fluid structure at the vicinity of nanoparticle due to its higher specific surface area. Apart from this, nanoparticle aggregation was identified as the key mechanism in governing thermal conductivity enhancement. It was iv observed that the thermal conductivity enhancement of aggregated nanofluids is higher compared to non-aggregated nanofluids by up to 35%. Based on the decomposition of thermal conductivity that is divided into three modes, namely collision, potential and kinetic; the greater enhancement in aggregated nanofluids was attributed to both higher collision amongst particles and increase in potential energy of nanoparticles to allow effective heat conduction along the backbone of aggregation. Consequently, based on the examination on thermal conductivity and viscosity enhancement, the efficiency of nanofluids was improved by increasing particle size and temperature. The thermal conductivity enhancement increases with increasing particle size but independent of temperature; whereas the viscosity enhancement decreases with increasing particle size and temperature. The particle size variation was therefore shown to be more effective than temperature control.